2019
DOI: 10.1002/esp.4711
|View full text |Cite|
|
Sign up to set email alerts
|

Post‐fire soil erosion mitigation at the scale of swales using forest logging residues at a reduced application rate

Abstract: Mulching with forest residues has proved to be highly effective in reducing post‐fire soil losses at the plot scale. However, its effectiveness has not been quantified at the application rates that are typically used in operational post‐fire land management (2–3 Mg ha‐1 using straw), as well as at scales larger than 100 m2. The present study compared post‐fire erosion rates for six convergent hillslopes or swales of 500 to 800 m2, three of which were left untreated while the other three were mulched immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
2
19
4
Order By: Relevance
“…In fact, when our results were only compared during the three years of post-fire disturbance, the efficiency of mulch application decreased runoff by 7% and SY by 40%. Compared to Prats et al (2019Prats et al ( , 2012 where mulch application reduced runoff by 15%-25% and SY by more than five times, our results were more conservative probably because our burnt field area only represented 10% of the watershed area; while Prats et al (2012, 2019) calculated SY at the field area scale and they burned 100% of the area while in our case 10% of the catchment burned. Moreover, our simulations ran over 20 years vs. 5-10 years in other studies [32,61].…”
Section: Overall Landsoil Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…In fact, when our results were only compared during the three years of post-fire disturbance, the efficiency of mulch application decreased runoff by 7% and SY by 40%. Compared to Prats et al (2019Prats et al ( , 2012 where mulch application reduced runoff by 15%-25% and SY by more than five times, our results were more conservative probably because our burnt field area only represented 10% of the watershed area; while Prats et al (2012, 2019) calculated SY at the field area scale and they burned 100% of the area while in our case 10% of the catchment burned. Moreover, our simulations ran over 20 years vs. 5-10 years in other studies [32,61].…”
Section: Overall Landsoil Resultscontrasting
confidence: 66%
“…Concerning sediment reduction caused by mulching, Shakesby et al (1996) [63], showed that Eucalyptus logging litter reduced soil erosion by 95%. The average reduction was five times in Prats et al (2019Prats et al ( , 2012; it should be noted that, in the latter study, maximum erosion rates were lower than in our study site. As previously said, the study site of Prats et al (2012) also presents smaller temporal and spatial scales.…”
Section: Overall Landsoil Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…The experiment revealed, indeed, that it was the lowest effective straw application rate. Other materials, such as wood strands and forest residues are known to be more resistant to be blown away by wind (Robichaud et al, 2014;Prats et al, 2019).…”
Section: Straw and Straw-biochar Mulch Effects On Om Exportsmentioning
confidence: 99%
“…The first can be achieved by using post-fire mulching. The application of a layer of straw of 2 Mg ha -1 over the soil is the most effective soil erosion mitigation treatment and its effectiveness has been extensively monitored in the USA (Robichaud et al, 2014;2020) and Europe (Fernandez & Vega, 2016;Prats et al 2019). However, the perception of forest managers is that post-fire mulch is expensive and they are reluctant to use straw mulching and most post-fire expenditures are used for logging, barrier-based or planting/seeding solutions instead.…”
Section: Introductionmentioning
confidence: 99%